DAMPAK RISIKO PANDEMI DAN FAKTOR UTANG TERHADAP RETURN AWAL SAHAM IPO PADA TAHUN 2020 - Kuswanto, Randy (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to obtain empirical evidence about the effect of pandemic risk and debt factors on stock’s initial return. Prior studies suggested initial return is influenced by multiple determinants. This study combines debt disclosures, debt retirement ratio and pandemic risk as a model to be analyzed and captured theirs impact on initial public offering return. The population in this study is all new public listed companies in Indonesia Stock Exchange in 2020. Purposive sampling is used as a sampling method to collect 48 samples. This study generates multiple linear regression method to test the hypotheses. The result of this study shows only pandemic risk has statistically significant influence on initial return. Firm who stated COVID-19 pandemic as a risk factor to its prospectus tend to lower their initial return by -13,5%. As a final result, this study provides empirical evidence that pandemic factor can be significant variable to be considered especially for capital market study during COVID-19 pandemic period.